Influence of gold nanoparticles on wound healing treatment in rat model: Photobiomodulation therapy. Issue 4 (12th November 2016) - Lau, PikSuan; Bidin, Noriah; Islam, Shumaila; Shukri, Wan Norsyuhada Binti Wan Mohd; Zakaria, Nurlaily; Musa, Nurfatin; Krishnan, Ganesan
Abstract : Background and Objective: The aim of this study is to investigate the effect of gold nanoparticles (AuNPs) in photobiomodulation therapy (PBMT) on wound healing process. Materials and Methods: AuNPs are synthesized by Q‐switched Nd:YAG laser ablation technique. Cutaneous wound are induced on 45 Sprague Dawley rats on its dorsal part and then randomly divided into three groups. One group serves as non‐treatment group (GC) and another two groups are subjected to AuNPs with and without PBMT. About 808 nm diode laser with output power of 100 mW is used as a light source for PBMT. The treatment was carried out daily with exposure duration of 50 seconds and total fluence of 5 J/cm 2 . Wound area is monitored for 9 consecutive days using a digital camera, and histological examination is performed at 3rd, 6th, and 9th day through hematoxylin and eosin stain as well as Masson's trichrome stain. Results: The group of rats subjected to AuNPs with PBMT shows significantly accelerated wound closure compared to other groups. Histological results indicate that AuNPs and PBMT group is more effective in stimulating angiogenesis and triggers inflammatory response at early stage. Conclusion: The application of AuNPs in PBMT has potential to accelerate wound healing due to enhanced epithelialization, collagen deposition and fast vascularization. Lasers Surg. Med. 49:380–386, 2017. © 2016 Wiley Periodicals, Inc.